Sistem Kepengurusan Administrasi Kependudukan Cetak Ulang KTP di Wilayah Kelurahan Alun-Alun Contong - Rassel Putra Adhia; Budi Prabowo (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
In Indonesia, there are still many residents who still lack understanding of the administration of population administration. This research aims to examine the population administration management system in Alun-Alun Contong Village, Surabaya. With a focus on the implementation of digital information technology in population data management. The research methods used include direct observation and interviews with village officials. The results showed that Alun-Alun Contong Village has implemented a digitalization system through the Klampid New Generation (KNG) application, which makes it easier for residents to take care of population documents. However, there are still obstacles such as the lack of socialization to the community and limited access to technology for some residents. The conclusion of this research is that there is a need for increased socialization, training for village officials, and improved technological infrastructure to support a more efficient and inclusive administrative system. This research is expected to be a reference for local governments in an effort to improve the quality of population administration services in urban village areas